Discrepancy in the legislative regulations governing the education of advocates in Indonesia - Nurhasanah, Nurhasanah; Sayuti, Sayuti; Idriz, Mesut (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
This paper aims to describe the legal confusion that arose after the Minister of Research and Technology of Higher Education Regulation No. 5 of 2019 on the Advocate Professional Program was passed. One of the clauses in this regulation has stipulated that the Advocate Education Program is organized by a tertiary institution that has the accreditation value “B” and collaborates with advocate organizations while the Constitutional Court Decision stipulates that Advocate Professional Special Education is organized by Advocate Organizations in collaboration with tertiary institutions that have the accreditation value “B”. In addition, the factors that cause the legal confusion and how it affects the advocate education after disharmony are also the focus of this article. To reveal the various legal perceptions related to this theme, the author uses a qualitative method with a juridical normative approach. The data and information can be had by data of library and the several articles related to up-to-date themes in Indonesia. The conclusion in the article is that the legal chaos that occurred was caused by the factor of sectoral ego, the law-making factor, the weakness of Legal education, and the accountability of Advocate Education Financing. second, the implementation of advocate education had not yet had the formulation and standards, both for the Ministry of Research, Technology and Higher Education, that it is all legal education in tertiary institutions and for the various advocate organizations. To anticipate the four issues that have been discussed, it is deemed necessary to conduct legal deliberations in providing win-win solutions.